MANGROVE FOREST FRAGMENTATION BECAUSE OF SUN AND BEACH TOURIST DEVELOPMENT IN THE NORTHERN PACIFIC OF COSTA RICA: A CASE STUDY - Bravo-Chacón, Juan; Picón-Cruz, Juan Carlos; Rodríguez-Quirós, Rigoberto (Revista Geográfica de América Central., 2014)
Tourism along the Pacific coast of Costa Rica has led to significant changes in mangrove ecosystems. There has been a substitution of this forest type for another more adapted to widespread tourist concepts, such as the existence of palm trees. These substitution processes involve the movement of species, mangrove removal and habitat reduction for different flora and fauna species. This is due mainly to economic criteria, where spaces in the tourist imaginary are attempted to be recreated, thereby scarifying the original natural heritage landscape and replacing it with scenery more customary to international standards of sun and beach tourism. This article aims to raise awareness of the changes and to show that the original mangrove ecosystems envelope unmeasured richness that have not yet been calculated in biodiversity terms.